Peter Salner: Budúci rok v Bratislave alebo stretnutie. [Next Year in Bratislava or a Meeting.] : Bratislava: Albert Marenčin PT, 2007, 200 pp. - Soukupová, Blanka (Lidé města, 2010)
A review of the book by Peter Salner.